Cell deformation and acquired drug resistance: elucidating the major influence of drug-nanocarrier delivery systems. Issue 9 (5th February 2020) - Nandi, Semonti; Kale, Narendra R.; Takale, Vijay; Chate, Govind C.; Bhave, Madhura; Banerjee, Shashwat S.; Khandare, Jayant J.
Abstract : Chemo-cycles of doxorubicin-nanocarriers are reported to be highly indicative of cell deformations and are a progressive indicator of acquired drug resistance. Abstract : Cancer diagnosis and its stage-wise assessment are determined through invasive solid tissue biopsies. Conversely, cancer imaging is enriched through emission tomography and longitudinal high-resolution analysis for the early detection of cancer through altered cell morphology and cell-deformation. Similarly, in post multiple chemo-cycle exposures, the tumor regression and progression thereafter are not well understood. Here, we report chemo-cycles of doxorubicin (Dox) carrying nanoparticles (NPs) to be highly indicative of cell deformation and a progressive indicator of phenotypic expressions of acquired drug resistance (ADR). We designed graphene (G) based nanocarriers by chemically conjugating multiple components: (i) G; (ii) iron oxide (Fe3 O4 ) NPs; and (iii) Dox through a cysteine (Cys) linker (G-Dox and G-Cys-Fe3 O4 -Dox). Although Dox underwent cell diffusion, the G-based nanocarriers followed a receptor-mediated endocytosis which created a profound impact on the cell membrane integrity. ADR owing to Dox and G-based nanocarriers was analyzed through a cytotoxicity assay, cell morphology deformation parameters and cellular uptake kinetic patterns. Interestingly, after the third chemo-cycle, G-Dox incubated cells showed the greatest decrease in the alteration of the nuclear surface area (NSA) of ∼28%, a ∼40% reduction of the cell surface area (CSA) and a ∼32% increase in the cell roundness (CRd). Our results suggested that the G-based nanocarriers induced the cell deformation process, subsequently resulting in ADR. Although the G-based nanocarriers initiated ADR, G-Dox was most cytotoxic to cancer cells and induced the maximum cell morphology deformation within our scope of study. This outcome implies caution is needed when using G-based nanocarriers and other multi-component nanosystems for Dox delivery as they lead to possible phenotypic expressions of drug resistance in cancer cells.